Care Provided to Women Victims of Intimate Partner Violence From the Perspective of Health Professionals - Jordana Brock Carneiro PhD; Nadirlene Pereira Gomes PhD; Fernanda Matheus Estrela PhD; Andrey Ferreira da Silva PhD; Milca Ramaiane da Silva Carvalho PhD; Natália Webler BSc (SAGE Publishing, 2022)
Intimate Partner Violence (IPV) is a recurring phenomenon in society and can have important repercussions for the lives and health of women worldwide. Even in this alarming global scenario, many health workers still have difficulties approaching IPV with women and providing care for the victims of this type of violence. Given this context, this qualitative study aims at understanding how primary health care professionals provide care for women victims of violence by intimate partners. In view of the methodology design proposed in the Grounded Theory, data collection took place through theoretical sampling. Data collection was carried out in 22 institutions offering primary health care, with 31 female workers from different professional categories being interviewed individually and in depth, including physicians, nurses, dentists, psychologists, and social workers. The results show that, in order to overcome the difficulties encountered in caring for victims of IPV, primary health care workers have been developing strategies for the care of these women. These strategies include identification of such cases through questions about the woman's intimate relationship, by establishing a bond with the victim so that she feels welcomed, and through articulation with other team professionals to propose expanded health care. The interventions carried out by these professionals include meeting the demands of women in the health institution where they work, referral to other services in the network, if necessary, and notification of IPV cases to epidemiological surveillance. Based on this understanding of the care offered by the professionals to women who are victims of IPV in primary health care, the research aims at contributing to the sensitization of professionals working in health institutions regarding the identification of signs that raise suspicion of IPV, as well as at addressing such cases in a way to fully meet these women's needs.